Galleri Flash. - Brandts Klaedefabrik, Odense; Galleri Flash - Brandts Klaedefabrik, Odense (Odense : Galleri Flash - Brandts Klaedefabrik)
Kramer, Per ; Balsgaard, Jane ; Mikkelsen, Leif ; Hvid, Hans Jorgen ; Fomsgaard, Jes ; Pedersen, Felix ; Bonanno, Alfio ; Martin, Harvey ; Diedrichsen, Ulla ; Troelsen, Frede ; Ronnau, Jorn ; Junichi-Inoue ; Jensen, Jan ; Holdensen, Annette ; Folmer Hansen, Ole ; Oldau Krull, Hans
Deens
boek